Ecodevelopment: An Imperative to National Development - Sharma, Laxman Prasad (Tribhuvan University Journal, 2010)
Not available. Key words: Ecodevelopment; National Development Tribhuvan University Journal Volume, XVI, 1993 Page: 78-86 Uploaded date: 4 October, 2010